Pengaruh Harga terhadap Tingkat Penjualan Tiket pada Makmur/Halmera (Analisis SWOT) - Sitorus, Risky Manuntun Agus Pranata; Sitanggang, Eva Rianty Angelina; Edward A. Lbn. Raja (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of price on ticket sales at PT. Makmur/Halmahera using the SWOT analysis method. PT. Makmur/Halmahera faces price competition from competitors offering cheaper tickets, as well as limitations in adapting to online ticketing technology. Ticket sales data from April, May, and June 2024 were analyzed to evaluate sales fluctuations. The results showed that the premium pricing strategy of Rp215,000 per ticket created a perception of high quality but was less attractive to price-sensitive customers. In addition, the significant decline in sales 43.8% from April to May and 7.85% from May to June—indicates the need for innovation in services and promotional strategies. The SWOT analysis identified strengths such as service quality and company reputation, weaknesses in pricing and lack of innovation, opportunities to improve digital services, and threats from intense competition. Recommendations include developing an online ticketing system, improving service quality, and implementing aggressive digital promotions to enhance competitiveness and maintain customer loyalty.